2020
DOI: 10.1021/acssuschemeng.0c03230
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Intrinsic Mechanical Properties of Nanocrystalline Calcium Silicate Hydrate

Abstract: Nanocrystalline calcium silicate hydrate (C–S–H) is the binding phase of many low-CO2 cements. Understanding its structure–mechanical properties relationship is critical in designing sustainable concrete. For the first time, a similar basal spacing (only 0.17 Å variation) of C–S–Hs at Ca/Si ratios of 0.8–1.5 is prepared via coprecipitation. The C–S–H nanostructure is determined using X-ray absorption spectroscopy, and the intrinsic nanomechanical properties of C–S–H at various Ca/Si are measured using high-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(8 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…1b, the CSH has a layer-stacked structure composed of intralayer Ca and wollastonite type Si chains. 22,23 When the molar Ca/Si ratio is 1, there are some distorted interlayer Ca atoms between layers, 23 which prefer to react with CO 2 in desilication solution and form by-product CaCO 3 . 17 While, in the presence of Acumer2000, the carboxyl groups can recognize and chelate to Ca( ii ) ions, and its carbon chains with sulfonic groups can give rise to steric and electrostatic repulsion.…”
Section: Resultsmentioning
confidence: 99%
“…1b, the CSH has a layer-stacked structure composed of intralayer Ca and wollastonite type Si chains. 22,23 When the molar Ca/Si ratio is 1, there are some distorted interlayer Ca atoms between layers, 23 which prefer to react with CO 2 in desilication solution and form by-product CaCO 3 . 17 While, in the presence of Acumer2000, the carboxyl groups can recognize and chelate to Ca( ii ) ions, and its carbon chains with sulfonic groups can give rise to steric and electrostatic repulsion.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon can be confirmed by the formation of Ca-OH bonds in the C-S-H. M.J. Abdolhosseini Qomi [ 26 ] found that more Ca-OH bonds formed through water molecules dissociated and condensed into silica chains when the Ca/Si ratios increased from 1.1 to 2.0. This Ca-OH bond was pH dependently [ 27 ]. The other possible explanation is that outer C-S-H can grow on the surface of nano-CH particles [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the approximate compositions of PC, MSWI ash, and industrial byproducts (coal fly ash, silica fume, and ground granulated blast-furnace slag (GGBFS)). [61,[64][65][66]). C-S-H is mesoporous with high surface areas.…”
Section: Concretementioning
confidence: 99%
“…Figure 1. Schematic diagrams of concrete at different scales (derived from[61,[64][65][66]). C-S-H is mesoporous with high surface areas.…”
mentioning
confidence: 99%